Le lettere di Dante. Ambienti culturali, contesti storici e circolazione dei saperi - Montefusco, Antonio (Toscana Bilingue. Storia sociale della traduzione medievale / Bilingualism in Medieval Tuscany, 2020)
Notwithstanding an impressive amount of secondary literature, an exhaustive study has been never devoted to the twelve letters written by Dante Alighieri after his banishment from Florence (1302-1315). This book answers to this important need of Dante Studies, offering an important tool for the increasing community of specialists interested in Dante's works and posterity linked to the seventh centenary of his death (2021). A section is devoted to study in depth the theory and practice of the dictamen of the age in relationship with the concrete style of Dante's texts. A preliminary overview is provided by Latin Philologists and Paleographers on the subject of the manuscript trasmission envisaging the problems dealing with the critical editions of the texts. Example of political communication realized by a layman, the papers gathered in this volume intend to offer a new reading and interpretation of these important letters, studying them in their socio-cultural context.